Polarization Singularity Explosions in Tailored Light Fields. Issue 6 (2nd May 2018) - Otte, Eileen; Alpmann, Christina; Denz, Cornelia
Abstract: Complex propagation dynamics of higher‐order polarization singularities are investigated within tailored Poincaré beams. Spatial polarization modulation and additional phase vortices of higher strength are combined, evoking polarization singularity splitting, type conversion, creation and annihilation. These phenomena form singularity "explosions" along their longitudinal evolution. These dynamics of propagating customized light fields and embedded singularities are analyzed experimentally and numerically. Furthermore, similarities of polarization singularity explosion and phase vortex unfolding are discussed, exploring fundamental propagation and spatio‐temporal interaction properties of optical singularities. Abstract : Optical singularities belong to the most fundamental properties of light. Besides appearing naturally, higher‐order singularities can be realized artificially implementing structured light fields. Combining spatial polarization and phase modulation, unstable scalar and vectorial singularities are superimposed and their complex propagation dynamics are studied in a slightly perturbed system. Singularity "explosions" are observed including singularity unfolding, type conversion, creation and annihilation.